2014
DOI: 10.3324/haematol.2014.103853
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 1 abnormalities in elderly patients with newly diagnosed multiple myeloma treated with novel therapies

Abstract: ABSTRACT(<10%) and is considered an adverse prognostic factor in young patients. 15,16 The relevance of chromosome 1 (chr1) abnormalities has been reported in several studies: Shaughnessy et al. defined a 70-gene high-risk signature, in which 30% of genes mapped to chr1, suggesting the significant poor prognostic impact of gain(1q) and del(1p). 17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
(65 reference statements)
1
17
0
1
Order By: Relevance
“…Upon progression of the disease, MM cells accumulate additional genetic alterations, such as recurrent losses of 13q14 and 17p13 and gains of 1q21 and 9q34. The translocations t(14;16), t(14;20), t(4;14) as well as gains of 1q21 and losses of 17p13 and, to some extent, also 13q14 deletions were defined as high risk factors (Fonseca et al , ; Munshi et al , ; Munshi & Avet‐Loiseau, ; Neben et al , ; Shaughnessy et al , ), although there is some evidence that initial treatment with novel agents, e.g., the proteasome inhibitor bortezomib, may overcome the adverse prognosis of an underlying t(4;14) or 17p13 deletion (Avet‐Loiseau et al , ; Bergsagel et al , ; Caltagirone et al , ; Neben et al , ; Sonneveld et al , ). In addition, bortezomib was also described to have a positive influence in relapsed/refractory MM (Dimopoulos et al , ; Richardson et al , ; Walter‐Croneck et al , ).…”
mentioning
confidence: 99%
“…Upon progression of the disease, MM cells accumulate additional genetic alterations, such as recurrent losses of 13q14 and 17p13 and gains of 1q21 and 9q34. The translocations t(14;16), t(14;20), t(4;14) as well as gains of 1q21 and losses of 17p13 and, to some extent, also 13q14 deletions were defined as high risk factors (Fonseca et al , ; Munshi et al , ; Munshi & Avet‐Loiseau, ; Neben et al , ; Shaughnessy et al , ), although there is some evidence that initial treatment with novel agents, e.g., the proteasome inhibitor bortezomib, may overcome the adverse prognosis of an underlying t(4;14) or 17p13 deletion (Avet‐Loiseau et al , ; Bergsagel et al , ; Caltagirone et al , ; Neben et al , ; Sonneveld et al , ). In addition, bortezomib was also described to have a positive influence in relapsed/refractory MM (Dimopoulos et al , ; Richardson et al , ; Walter‐Croneck et al , ).…”
mentioning
confidence: 99%
“…A previous study also reported that the frequency of CNAs was highest in chr 1. Especially, elderly patients aged 65 years or older are more likely to have abnormalities when they are treated with novel therapies [1]. Also, the copy number of the genes in the 1q21 region, which showed the most chromothripsis-like patterns, was amplified in resistant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a malignant disease caused by an abnormal proliferation of plasma cells [1]. According to the 2014 Ministry of Health and Welfare Cancer Registration Statistics, MM is the third most common cancer among hematologic malignancies in Korea [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thalidomide maintenance was associated with higher toxicity, including neuropathy, constipation, elevated creatinine, and skin toxicity [108]. In patients treated onstudy with VMPT-VT versus VMP, thalidomide maintenance was felt to be associated with worse OS in patients harboring abnormalities in chromosome 1 (HR 3.08, 95 % CI 1.04-9.14, p = 0.042) or deletion 17p (HR 4.28, 95 % CI 1.59-11.54, p = 0.004) [109].…”
Section: Maintenance Therapymentioning
confidence: 98%